2016
DOI: 10.1007/s11695-016-2390-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes in Patients with Morbid Obesity and Type 1 Diabetes Undergoing Bariatric Surgery

Abstract: Bariatric surgery in patients with T1DM mainly provides benefits of weight reduction, on insulin requirements, obesity comorbidities, and some benefits in diabetes complications, but might have only minimal effect on the glycemic control in the long term. This trial was registered at www.controlledtrials.com as ISRCTN49980913.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…They concluded that bariatric surgery in patients with type 1 diabetes mellitus largely provides benefits of insulin requirements and some advantages related to the diabetes complication but have no effect on the glycemic control in the long term. (39) In another study, it was shown that longer duration of diabetes is associated with increasing age. They pointed that shorter duration of diabetes lead to patients with good metabolic response (1.75 ± 0.69 vs. 8.79 ± 2.8 years) and chance of complete remission after gastric bypass surgery was more in patients with a diabetes duration < 5 years.…”
Section: Discussionmentioning
confidence: 97%
“…They concluded that bariatric surgery in patients with type 1 diabetes mellitus largely provides benefits of insulin requirements and some advantages related to the diabetes complication but have no effect on the glycemic control in the long term. (39) In another study, it was shown that longer duration of diabetes is associated with increasing age. They pointed that shorter duration of diabetes lead to patients with good metabolic response (1.75 ± 0.69 vs. 8.79 ± 2.8 years) and chance of complete remission after gastric bypass surgery was more in patients with a diabetes duration < 5 years.…”
Section: Discussionmentioning
confidence: 97%
“…We believe that such patients may include some SPIDDM cases because it is difficult to distinguish SPIDDM from T2DM. Additionally, as in the present study, others have indicated the possibility of hypoglycemic attack after surgery . Patients with DM should be provided adequate education about nutrition after surgery, such as an appropriate diet and nutritional requirements, to prevent a hypoglycemic attack.…”
Section: Discussionmentioning
confidence: 53%
“…Although the subjects in this study achieved good weight loss and glycemic control of HbA1c and reduced their insulin requirements, there are some negative effects after surgery in T1DM patients. Some articles have shown that BS in patients with T1DM cannot achieve sufficient glycemic control of HbA1c . As such, we have to monitor our subjects strictly because their glycemic control will probably get worse.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was associated with a significant reduction in bodyweight, insulin requirements, improvement of obesity comorbidities and some diabetes complications. 102 However, there was only a marginal effect on glycaemic control in treated patients on long-term follow-up.…”
Section: Bariatric Surgery For Type 1 Diabetes Mellitusmentioning
confidence: 98%